ESENSI DAN URGENSI KAJI TINDAK PARTISIPATIF DALAM PEMBERDAYAAN MASYARAKAT PERDESAAN BERBASIS SUMBERDAYA PERTANIAN (Forum Penelitian Agro Ekonomi, 2024)
It is believed that action research has been numerously implemented for a long time in Indonesia. Nevertheless, it can be generally stated that its implementation was relatively lack in accommodating farmer’s aspiration. As a result, a method of participatory action research needs to be recommended. This article aims to review the essence and urgency of participatory action research focused on rural community-based agricultural empowerment. At least, there are three pillars of participatory action research towards community empowerment, namely participation, facilitation, and intervention. However, the implementation of participatory action research is time-consuming and depends on community’s initiative in determining needs priority. Interactive participation and creativity through participation as well as democracy-based facilitation and intervention should be carried out. Hence, it is implied that the development of community’s aspiration (button-up approach) still requires top-down approach, which is free from paternalistic attribute.